The Effect of Triptolide Combined With Crocin on Arthritis in Mice: From Side Effect Attenuation to Therapy - Yan, Min; Yan, Yinyin; Zhang, Zhenqiang; Wang, Guoqiang; Shi, Wenbo; Jiang, Mengyuan; Zhao, Junwei; Wu, Xiangxiang; Zeng, Huahui (Frontiers in Pharmacology, 2022)
Clinical use of triptolide (TP) is restricted due to severe toxicity. This study assessed the protective effect of crocin (CR) as a natural antioxidant against TP-induced toxicity in bovine collagen type II-induced arthritis (CIA) in mice. The mice in the CIA model group showed macroscopic signs of severe arthritis. The anti-arthritis effects in the control, TP+CR, and TP groups were evaluated through assessment of foot volume, arthritis score, and proinflammatory cytokines, and collagen antibody assay. Crocin reduced TP-induced toxicity, as evidenced by evaluation of survival rate, body weight, visceral index, hepatic and renal functions, histopathologic analyses, and antioxidant enzyme activities. Transcriptome sequencing resulted in identification of 76 differentially expressed genes (DEGs) associated with hepatotoxicity between the TP and TP+CR groups. Of these, Three DEGs (Cyp1a2,Gsta4, and Gstp1) were validated using quantitative real-time PCR analysis. In conclusion, CR protected CIA mice from TP-induced toxicity through modulation of the cytochrome P450 and glutathione metabolism pathways.